2020
DOI: 10.3892/etm.2020.9493
|View full text |Cite
|
Sign up to set email alerts
|

Interaction network of immune‑associated genes affecting the prognosis of patients with glioblastoma

Abstract: Glioblastoma multiforme (GBM) is a common malignant tumor type of the nervous system. The purpose of the present study was to establish a regulatory network of immune-associated genes affecting the prognosis of patients with GBM. The GSE4290, GSE50161 and GSE2223 datasets from the Gene Expression Omnibus database were screened to identify common differentially expressed genes (co-DEGs). A functional enrichment analysis indicated that the co-DEGs were mainly enriched in cell communication, regulation of enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Immunotherapy is a significant and popular approach in preventing and treating tumors [ 30 ]. Presently, increasingly more studies have been exploring new prognostic biomarkers associated with the tumor immune microenvironment, including LGG.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy is a significant and popular approach in preventing and treating tumors [ 30 ]. Presently, increasingly more studies have been exploring new prognostic biomarkers associated with the tumor immune microenvironment, including LGG.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells in GBM generated a proangiogenic and inflamed microenvironment, which recruited immune cells and molecules to infiltrate the tumor mass, leading to intricate immune networks in GBM [ 39 ]. Emerging evidence has demonstrated that immune networks consisting of multiple immune components in the tumor microenvironment could characterize the immune phenotypes of tumors and impact the clinical outcomes of GBM patients [ 17 , 18 ]. Due to the essential role of immune networks and their diverse presence in GBM, this study performed clustering analysis based on IRGs, which may contribute to the understanding of GBM heterogeneity and facilitate individualized treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that immune networks are inextricably linked to cancer initiation and progression, with the ability to predict prognosis and guide treatment for tumor patients [ 15 , 16 ]. Hou et al have demonstrated that the immune‐regulatory interaction networks were tightly associated with unfavorable prognosis of GBM patients [ 17 ]. The interplay between tumor cells and the immune microenvironment in GBM ultimately suppresses the beneficial pattern of molecular pathways, improving its malignancy and elevated resistance to cancer therapy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%